Pengaruh Tenur Audit, Reputasi KAPdan Komite Audit Terhadap KualitasLaba (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2010-2013) - Deri Permana (Wahana Riset Akuntansi, 2015)
This research is aimed to examine and find out empirical evidence of the audit tenure, KAP’s reputation and audit comitee on earnings quality. Sampled used in this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) during period 2010-2013. The data are collected using purposive sampling method. The analysis of this research employs multiple regression. Result show that audit tenure have significant effect on earnings quality, KAP’s reputation have not significant effect on earnings quality and audit comitee have not significant effect on earningsquality.Keyword : audit tenure, KAP reputation, audit comitee, earnings quality